Diagnosed, Identified, Current and Complete Depression Among Patients Attending Primary Care in Southern Catalonia: Different Aspects of the Same Concept. - Montesó-Curto, Pilar; Ferré-Grau, Carme; Lleixà-Fortuño, Mar; Albacar-Riobóo, Nuria; Lejeune, Marylene (Archives of Psychiatric Nursing, 2014)
The aims of this study were to explore the prevalence and the conceptualizations of depression detected by the healthcare system, identified by the patient or classified/identified in the validated Goldberg's questionnaire in a community. We conducted a cross-sectional evaluation of 317 patients. The different types of depression diagnosed, identified, current or total were stratified by age and gender groups. The difference in the conceptualization of depression from the medical or ordinary people point of view indicate that depression care requires the understanding of the lifestyle, beliefs, attitudes, family and social networks of the people the physicians and nurses care for.